The space between : experience, context, and process in the therapeutic relationship - Flaskas, Carmel; Mason, Barry, Dr; Perlesz, Amaryll (Systemic thinking and practice series., 2005)
This book focuses on the therapeutic relationship between the family and the therapist, an element present in every therapy session. Clinical examples are found throughout the book to illustrate both positive and negative outcomes of therapy. Part of the Systemic Thinking and Practice Series.